Anthropological perspectives on CKDnt in Mexico: time for a paradigm shift on the social determinants of health - Kierans, Ciara; Padilla-Altamira, Cesar (Frontiers in Nephrology, 2023)
In Mexico, the kidneys of individuals in poor and marginalized communities are failing with little warning and no explanation. Commonly referred to as chronic kidney disease of non-traditional origin (CKDnt), this new variant of kidney disease cannot be accounted for by conventional or discrete etiological explanations, but is instead understood to be a consequence of economic development, environmental degradation and precarious working and living conditions. Drawing on two interconnected ethnographic studies, and the intertwining problems of causation and care, this paper will (1) document the social conditions of disease emergence around Lake Chapala, Central Mexico, and (2) follow the haphazard routes kidney patients take to access resource-intensive biotechnical treatments. Its aim is to both challenge and reconceptualize social determinants as social relations in order to fully account for the profoundly contextual, temporal, and dynamic character of this condition, and to rethink opportunities for care and intervention.